The RELATIONSHIP BETWEEN WORKLOAD AND WORK STRESS IN NURSES IN THE EMERGENCY DEPARTMENT OF BAHTERAMAS GENERAL HOSPITAL IN SOUTHEAST SULAWESI PROVINCE - noviati novi (STIKes Mandala Waluya Kendari, 2019)
background: Workload is closely related to the productivity of health workers, which 53.2% of the truly productive time is spent on direct health services and the remaining 39.9% is used for supporting activities. Health workers, especially nurses, which the workload analysis can be seen from some aspects such as tasks based on their main function, additional works which are done, number of patients to be treated, work capacity according to the education he obtained, and working time to do the works. Excessive workload will lead to stress, which is usually dominated by somatic complaints, for example how a person's body responds when he is experiencing excessive workload. Methods: This type of research is an analytic survey with cross sectional design that is a research design to determine the relationship of workload with work stress on nurses in Emergency Room Installation of Emergency Services Bahteramas General Hospital, Southeast Sulawesi Province, with a total sample of 38 respondents. Results: The results obtained are significant p = 0,000 <0.05, with a Pearson Correlation value of 0.782 correlation, which means that the correlation is very strong, so it can be seen that there is a relationship between workload and work stress The amount of influence (r) workload on stress, if calculated determinant coefficient (R) or (r) 2, then (0.782) 2x100% = 61.2%. This means that 61.2% workload contributes to the incidence of work stress.Conclusion: Based on the results obtained it can be concluded that there is a relationship between workload and work stress of nurses at IGD BLUD Bahteramas General Hospital in Southeast Sulawesi Province.